Keadilan Restoratif Dalam Penyelesaian Kasus Tindak Pidana Kekerasan Dalam Rumah Tangga (KDRT) di Wilayah Hukum Polresta Padang - Hadiid Akram; Fadillah Sabri; Iwan Kurniawan (Fakultas Hukum Universitas Andalas, 2023)
Generally, the resolution of a criminal case takes place through the criminal justice process, but it is not excluded that it can be resolved through other mechanisms. In the legal jurisdiction of Polresta Padang, there is a facility called Palanta Mediation. Palanta Mediation is one of the facilities for resolving criminal cases through mediation. One of the cases that can be resolved using the principles of restorative justice is domestic violence cases. The issues discussed concern the steps taken by the police at Polresta Padang in implementing restorative justice in handling domestic violence cases and the obstacles faced in applying the principles of restorative justice in handling domestic violence cases. The research method used is empirical juridical, by observing the phenomena that occur in the field in relation to applicable law. The police's steps in resolving domestic violence crimes involve bringing the parties together at Palanta Mediation. The obstacles faced by the police in resolving domestic violence crimes using restorative justice include inner conflicts that cannot be avoided, such as minor disputes between the parties